Multikulturalisme di Pondok Pesantren DDI Mangkoso Barru Sulawesi Selatan - Zulqarnain Zulqarnain (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2016)
This study talks about the embedded of the multicultural education values in Mangkoso boarding schools which the students comes from a variety of different areas with diverse cultures and tribes. They are then brought together and lived in an environment of boarding house that became the hallmark of boarding schools. This is a research field by using descriptive analysis methods that attempt to expose the systematic discussion of the materials which come from a variety of sources to then be analyzed carefully to obtain a result as a conclusion. The method of data collection is conducted through observation, interviews, and documentation. This research used sociological anthropology approach. The results of this research show the process of the embedded of the multicultural education values in boarding schools DDI Mangkoso conducted through several activities, such as; formal learning activities in school, activities of self development, and conditioning activities themselves. Whereas, the multicultural education values which is embedded in DDI Mangkoso boarding schools such as: democratic values and mutual tolerance value, appreciation and respect to each other, the embedded of social justice and equality values, and togetherness and help each other.